Pengaruh Gaya Kepemimpinan dan Teknologi Informasi Terhadap Kinerja Pegawai Melalui Motivasi Sebagai Variabel Intervening - Aldi, Mukhamad Fauzan; Mujanah, Siti; Fianto, Achmad Yanu Alif (MES Bogor, 2024)
This research uses a Partial Least Square (PLS) based Structural Equation Model (SEM) to examine the influence of leadership style and information technology on employee performance through motivation as an intervening variable. The research focused on the Pasuruan Regency Population and Civil Registry Service (Disdukcapil), with a population of 120 employees who are directly involved in the Management of the Population Administration Information System. A sample of 92 employees was selected using the Slovin formula as research respondents. The research results show that leadership style has a positive and significant direct influence on employee performance, as well as strongly influencing their motivation. Motivation has also been proven to have a very significant impact on employee performance. However, information technology does not have a significant direct effect on employee performance in the context of managing population administration information systems. However, information technology has a positive and significant impact on employee motivation, which indirectly improves their performance. A balance between an effective leadership style and the appropriate use of information technology in a dynamic and complex work environment is very important to increase employee motivation and performance at the Pasuruan Regency Dukcapil Office.